2017
DOI: 10.12709/mest.05.05.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things and the Man-in-the-Middle Attacks – Security and Economic Risks

Abstract: This paper presents some aspects of the Internet of Things (IoT) and attacks to which IoT may be exposed, above all, the man-in-the-middle (MITM) attack. After a short introduction, which describes the essence of the IoT and the MITM attack, used scientific methods and hypotheses are presented. The next chapters show the technology of MITM attacks and benefits that a successful attack provides to attackers. Here are presented also some of the most important examples of such attacks, which had a wider scope or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Attackers can redirect network traffic using Address Resolution Protocol (ARP) poisoning or by altering Domain Name System (DNS) settings or intercept HTTPS traffic by using self-signed certificates or tools such as (Secure Sockets Layer) SSL strip Fig. 2 A simple representation of a Man-in-the-Middle attack [19]. Many IoT devices do not verify the authenticity or the trust level of certificates, making the self-signed certificate method particularly effective.…”
Section: Man-in-the-middlementioning
confidence: 99%
See 2 more Smart Citations
“…Attackers can redirect network traffic using Address Resolution Protocol (ARP) poisoning or by altering Domain Name System (DNS) settings or intercept HTTPS traffic by using self-signed certificates or tools such as (Secure Sockets Layer) SSL strip Fig. 2 A simple representation of a Man-in-the-Middle attack [19]. Many IoT devices do not verify the authenticity or the trust level of certificates, making the self-signed certificate method particularly effective.…”
Section: Man-in-the-middlementioning
confidence: 99%
“…By doing this, mobile apps can locate new devices by probing every IP address on the local network for a specific port. An attacker can do the same thing to discover devices on the network [19]. An example of an MITM IoT attack is that of a smart refrigerator that could display the user's Google calendar.…”
Section: Man-in-the-middlementioning
confidence: 99%
See 1 more Smart Citation
“…Many cases of data and identity theft through hacked vehicles and hacked smart refrigerators have been previously reported. In 2014, a Samsung smart refrigerator, RF28HMELBSR, was a target of a man-in-the-middle attack to steal victims' Google credentials [22]. The hacking of Jeep Cherokee in July 2016 through MITM attack has also enabled hackers to access and control the vehicles' basic functions and consequently endangered the human life.…”
Section: A Geopolitical Risk and Threatsmentioning
confidence: 99%
“…The authors also suggested a countermeasure called Bloom filters and indicated the efficiency of the Bloom filter monitoring system. Cekerevac et al [29] showed a variety of attacks using MitM, including MIT-Cloud (MITC), MIT-Browser (MITB), and MIT-mobile (MITMO). They showed that MitM is not uncommon and can damage the IoT, even though it is an old attack.…”
mentioning
confidence: 99%